Assessing duplication and loss of APETALA1/FRUITFULL homologs in Ranunculales - Pabon-Mora, Natalia; Hidalgo, Oriane; Gleissberg, Stefan; Litt, Amy (Frontiers in Plant Science, 2013)
Gene duplication and loss provide raw material for evolutionary change within organismal lineages as functional diversification of gene copies provide a mechanism for phenotypic variation. Here we focus on the APETALA1/FRUITFULL MADS-box gene lineage evolution. AP1/FUL genes are angiosperm-specific and have undergone several duplications. By far the most significant one is the core-eudicot duplication resulting in the euAP1 and euFUL clades. Functional characterization of several euAP1 and euFUL genes has shown that both function in proper floral meristem identity, and axillary meristem repression. Independently, euAP1 genes function in floral meristem and sepal identity, whereas euFUL genes control phase transition, cauline leaf growth, compound leaf morphogenesis and fruit development. Significant functional variation has been detected in the function of pre-duplication basal-eudicot FUL-like genes, but the underlying mechanisms for change have not been identified. FUL-like genes in the Papaveraceae encode all functions reported for euAP1 and euFUL genes, whereas FUL-like genes in Aquilegia (Ranunculaceae) function in inflorescence development and leaf complexity, but not in flower or fruit development. Here we isolated FUL-like genes across the Ranunculales and used phylogenetic approaches to analyze their evolutionary history. We identified an early duplication resulting in the RanFL1 and RanFL2 clades. RanFL1 genes were present in all the families sampled and are mostly under strong negative selection in the MADS, I and K domains. RanFL2 genes were only identified from Eupteleaceae, Papaveraceae s.l., Menispermaceae and Ranunculaceae and show relaxed purifying selection at the I and K domains. We discuss how asymmetric sequence diversification, new motifs, differences in codon substitutions and likely protein-protein interactions resulting from this Ranunculiid-specific duplication can help explain the functional differences among basal-eudicot FUL-like genes.